(untitled) (Journal of Parents and Teachers, 2014)
Water is not an inexhaustible resource that is available to everyone, so it is essential to know ways to save, its efficiency and its conservation. For this reason, Zaragoza launched a campaign to raise awareness among the population (older and younger) about its use and the problems that this monopolizes if it is done in the wrong way. To do this, he organized talks at schools, various proposals on installation, collection and washing, water cards, water saving cards, etc.